2007
DOI: 10.1111/j.1365-2109.2007.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different oil cake sources on growth, nutrient retention and digestibility, muscle nucleic acid content, gut enzyme activities and whole-body composition in silver barb, Puntius gonionotus fingerlings

Abstract: Six iso-nitrogenous (30% crude protein) and iso-energetic (15 kJ g À1 ) diets were prepared using di¡erent oil cake sources, viz. groundnut, soybean, sun£ower, sesame, mustard and mixed oil cakes as major ingredients, and protein sources along with a minimum of 5% ¢sh meal in each diet and were fed to silver barb Puntius gonionotus ¢ngerlings (16.20 AE 0.11g) ad libitum four times a day close to an apparent satiation level for a period of 60 days to determine the e¡ect of diets on growth, nutrient utilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
15
1
2
Order By: Relevance
“…While the highest lipid ratio was obtained in 10SSM group, there was a decrease in the crude lipid of fish fillet in 15SSM and 20SSM groups. While the values obtained from the study showed similarity with the study of Mukhopadhyay and Kay (1999) who determined the crude lipid rates of fish fillet as 4.29 to 5.24%, they were lower than the studies of Emadi et al (2014), Jimoh et al (2014) and Mohanta et al (2007) who detected the crude lipid rates of fish fillet as 7.4%, between 5.73 and 5.87% and between 6.5 and 6.7%, respectively. In the above-mentioned studies, a visible reduction occurred in the crude lipid of fish fillet with increasing amount of sesame seed meal in the diet but the differences were not statistically significant (p˃0.05).…”
Section: Discussioncontrasting
confidence: 43%
“…While the highest lipid ratio was obtained in 10SSM group, there was a decrease in the crude lipid of fish fillet in 15SSM and 20SSM groups. While the values obtained from the study showed similarity with the study of Mukhopadhyay and Kay (1999) who determined the crude lipid rates of fish fillet as 4.29 to 5.24%, they were lower than the studies of Emadi et al (2014), Jimoh et al (2014) and Mohanta et al (2007) who detected the crude lipid rates of fish fillet as 7.4%, between 5.73 and 5.87% and between 6.5 and 6.7%, respectively. In the above-mentioned studies, a visible reduction occurred in the crude lipid of fish fillet with increasing amount of sesame seed meal in the diet but the differences were not statistically significant (p˃0.05).…”
Section: Discussioncontrasting
confidence: 43%
“…Puntius species is known to be a lean to moderate-fat fish. Nair and Gopakumar (1978) found that the Egyptian filamented barb (P. filamentous) contained 1.14% w.w. of TL in their muscle tissues (Henderson and Tocher, 1987), while the muscle fat of P. gonionotus ranges from 4 to 5% w.w. (Rahman et al, 1995;Mohanta et al, 2007). The muscle of R. borapetensis showed the lowest values for TL (0.86% w.w.) and M. nipponense the highest values (1.13% w.w.) compared to the other aquatic animal species in the present study (Table 1).…”
Section: Total Lipid (Tl)mentioning
confidence: 94%
“…The high cost of fish meal and concerns regarding its future availability have made it imperative for the nutritionists to reduce or eliminate the fish meal from fish and crustacean diets as a strategy to avoid any risk on the future of aquaculture industry (Muzinic et al., 2006; Brinker and Reiter, 2011; Kumar et al., 2011a; Oujifard et al., 2011). Substantial efforts have been made around the globe in evaluating the wide range of potential ingredients of plant (Mohanta et al., 2007; Nyina‐wamwiza et al., 2007; Erdogan and Olmez, 2010; Monentcham et al., 2010; Brinker and Reiter, 2011; Glencross et al., 2011; Kumar et al., 2011a,b; Oujifard et al., 2011) and animal (Guo et al., 2006; Muzinic et al., 2006; Yang et al., 2006; Yigit et al., 2006; Cavalheiro et al., 2007; Nyina‐wamwiza et al., 2007; Ahmad, 2008; Gümüş et al., 2009, 2010; Gümüş, 2011) origins. However, inclusion of plant protein above 25–50% of the total of the total diet frequently results in reduction of growth and/or high mortalities attributed to an improper balance of indispensable amino acids, a reduced digestibility of lipid and energy, the presence of antinutritional factors and/or the poor palatability (Nyina‐wamwiza et al., 2007).…”
Section: Introductionmentioning
confidence: 99%